2022
DOI: 10.1111/jonm.13800
|View full text |Cite
|
Sign up to set email alerts
|

Unfinished nursing care reasons as perceived by nurses at different levels of nursing services: Findings of a qualitative study

Abstract: Aim This study aimed to investigate reasons for unfinished nursing care across the whole levels of the nursing service as perceived by clinical nurses, ward managers and executive nurses. Background Even though unfinished nursing care has been considered an issue affected by the system, no studies to date have attempted to investigate reasons across the whole levels of the nursing service by involving clinical nurses, ward managers and executive nurses. Method A descriptive qualitative approach was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 32 publications
(56 reference statements)
0
41
0
Order By: Relevance
“…18,19 During emergency and disaster situations, clinical events that involve urgent patient situations, such as deterioration in patient conditions and sudden changes in patients' vital signs, were often given the highest priority over other care activities, such as ambulation, turning of patients, and feeding. [9][10][11] This review identified a potential distinction between types of missed nursing care before and during the pandemic. Before the pandemic, missed nursing care activities aimed to optimize patients' overall health and well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 During emergency and disaster situations, clinical events that involve urgent patient situations, such as deterioration in patient conditions and sudden changes in patients' vital signs, were often given the highest priority over other care activities, such as ambulation, turning of patients, and feeding. [9][10][11] This review identified a potential distinction between types of missed nursing care before and during the pandemic. Before the pandemic, missed nursing care activities aimed to optimize patients' overall health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Unfavorable working conditions, poor collegial relations, negative safety culture, poor ethical climate, and lack of management and organizational support were likewise associated with an increased incidence of nursing care left undone. 8,9 Missed nursing care, recognized as a threat to patient safety, has been consistently cited as a precursor to serious adverse events, 10 increased re-hospitalization and mortality rates, 11 and an overall decline in nursing care qual-ity. 6 It is often linked with an increase in nurses' dissatisfaction 5 and eventual turnover.…”
mentioning
confidence: 99%
“…At the overall level, reasons for UNC have emerged at the healthcare system, unit, nurse and at patient level; previous studies investigating the perceptions of nurses 34 , 35 , 36 have identified the reasons at the system, unit, nurse manager, clinical nurse and patient levels, thus suggesting that patients are able to identify the reasons for UNC at all levels, mirroring the perceptions of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…According to the only study available that collected patients' perceptions about UNC with a qualitative approach, 12 and considering the most recent studies investigating reasons for UNC as perceived by nurses, 34 , 35 , 36 a semistructured interview was designed. The interview was composed of the following open‐ended questions:…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have called the phenomenon of missed nursing care as cutting corners, referring to doing partial or omitting parts of patient care, delaying some types of care and doing things incorrectly (Jones et al, 2016). Chiappinotto and Palese (2022) study highlighted the complexity of nursing care that includes care units overflowing with high acuity patients, nurses with high workload demands, a lack material resources, systems which demand nursing time spent on documentation systems and management who have become accustomed to missed nursing care. Given these challenges it is not surprising that nurses are drawing on fast thinking in their day to day work.…”
Section: Dang Er S Of Nur S E S Thinking Fa S T With Older Patientsmentioning
confidence: 99%